1970
DOI: 10.1063/1.1693106
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Total and Total Line Radiation of Nitrogen, Oxygen, and Argon Plasmas

Abstract: Total radiation measurements for nitrogen, oxygen, and argon plasmas are presented for 2000Å < λ < 60 000Å and for temperatures from 9000 to 15 000°K. These data are compared to previous measurements for the total continuum and to theoretical calculations for the total line radiation. The line radiation was found to be of the same order of magnitude as the total continuum. Taking into account the effect of absorption in the total radiation measurements, a lower limit is obtained for the accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Other coefficients of the problem like C A p , C G p , k A , k G and σ were obtained from Ref. [9] for the temperature range 300 − 45000 K. Radiative losses from the arc were included by considering that the total radiation field is composed by ∼ 50% of continuous radiation and another 50% of line radiation [10,11]. The surrounding gas is considered to be transparent to continuous radiation but opaque to line radiation.…”
Section: ∂ ∂Zmentioning
confidence: 99%
“…Other coefficients of the problem like C A p , C G p , k A , k G and σ were obtained from Ref. [9] for the temperature range 300 − 45000 K. Radiative losses from the arc were included by considering that the total radiation field is composed by ∼ 50% of continuous radiation and another 50% of line radiation [10,11]. The surrounding gas is considered to be transparent to continuous radiation but opaque to line radiation.…”
Section: ∂ ∂Zmentioning
confidence: 99%
“…More interesting might be the fact that the volume of the nitrogen plasma column measured in this study was approximately half the size of the argon plasma (measured by Choi, 198 1 ), under similar operating conditions. Krey and Morris (1970) measured the total radiative power per unit volume for nitrogen and argon, and found that in the temperature range 12000 to 13 000 K, the radiation intensity of argon is higher than the corresponding intensity of nitrogen. The smaller volume of the nitrogen plasma coupled with its lower total radiation intensity can be of great economic importance, since it implies that, for a given temperature within the previously specified temperature range, the nitrogen plasma can transfer more power and at a higher efficiency to the anode of a transferred arc system than an argon plasma.…”
Section: Results and Discussion Section I -Solid Anodementioning
confidence: 99%
“…In order to dissipate the large heat flux into the wall, the arc vessel is usually constructed of water cooled copper rings, separated by insulators (Maecker (1956), Maecker (I960)). The wall stabilized arc has been used extensively for spectroscopic studies (Olsen (1963), Krey and Morris (1970), Bacri et al (1972)) and measurements of the transport properties of gases in the temperature range 7000 K to 20000 K (Emmons andLand (1962), Emmons (1967), Bues et al (1967), Bauder and Maecker (1971), Kopainsky (1971)). In the 1960's it was also studied extensively with a view to its application as a gas heater to produce high enthalpy gas flows for aerospace research (Stine and Watson (1964), Watson and Pegot (1967)).…”
Section: Introductionmentioning
confidence: 99%